Serological analysis of Ebola virus survivors and close contacts in Sierra Leone: A cross-sectional study. - Peter J Halfmann; Amie J Eisfeld; Tokiko Watanabe; Tadashi Maemura; Makoto Yamashita; Satoshi Fukuyama; Tammy Armbrust; Isaiah Rozich; Alhaji N'jai; Gabriele Neumann; Yoshihiro Kawaoka; Foday Sahr (Public Library of Science (PLoS), 2019)
The 2013-2016 Ebola virus outbreak in West Africa was the largest and deadliest outbreak to date. Here we conducted a serological study to examine the antibody levels in survivors and the seroconversion in close contacts who took care of Ebola-infected individuals, but did not develop symptoms of Ebola virus disease. In March 2017, we collected blood samples from 481 individuals in Makeni, Sierra Leone: 214 survivors and 267 close contacts. Using commercial, quantitative ELISAs, we tested the plasma for IgG-specific antibodies against three major viral antigens: GP, the only viral glycoprotein expressed on the virus surface; NP, the most abundant viral protein; and VP40, a major structural protein of Zaire ebolavirus. We also determined neutralizing antibody titers. In the cohort of Ebola survivors, 97.7% of samples (209/214) had measurable antibody levels against GP, NP, and/or VP40. Of these positive samples, all but one had measurable neutralizing antibody titers against Ebola virus. For the close contacts, up to 12.7% (34/267) may have experienced a subclinical virus infection as indicated by detectable antibodies against GP. Further investigation is warranted to determine whether these close contacts truly experienced subclinical infections and whether these asymptomatic infections played a role in the dynamics of transmission.